Some legal problems of criminal responsibility of legal entities abroad (Journal of actual problems of jurisprudence, 2016)
The problem of criminal responsibility of legal entities which can be examined as subjects of crime is examined in this article, for a criminal law not new and debatable enough. It is one of the most thorny and litigions problems of both foreign and domestic criminal law.Some cases of criminal responsibility of legal entities which can be attributed to the examples of collective responsibility are known in history of domestic criminal statute.
Keywords: criminal liability; a legal entity; the law; law; protection